Etienne Balibar in Conversation: Revisiting European Marxism - Barthold, Charles (Theory, culture & society, 2019)
In this interview, Balibar provides a number of reflections on the articulation of different Marxist traditions, including Italian Marxism and the Neue Marx Lektüre, to his own Althusserian position. Similarly, he comments on his relationship to the readings of French theory upon Marx?s oeuvre. He further develops an analysis of the contemporary challenges posed by capitalism ? and its different crises ? to critical theory, social sciences and social movements. Then, he argues that financialization and the Anthropocene are central issues. He concludes with thoughts on internationalism and citizenship, which he believes to be indispensable political elements in order to conceptualize resistance in this crisis context.